Monocyte-to-lymphocyte ratio is a promising biomarker in patients initially receiving hemodialysis - Xie, Aihua; Tang, Anna; Yang, Man; Xiong, Yuwan; Lin, Jieshan (Frontiers in Nephrology, 2025)
AimInflammation is very common among dialysis patients and can lead to an increase in morbidity and mortality. Monocyte-to-lymphocyte ratio (MLR) can serve as a reliable predictor of long-term survival in hemodialysis patients. However, few studies have addressed the role of MLR in patients initially receiving hemodialysis (within 3 months). In this study, we aimed to examine the association between MLR and the risk of cardiovascular and all-cause mortality in patients initially receiving hemodialysis.MethodsIn this study, a total of 216 patients newly receiving hemodialysis for at least 3 months were recruited. The associations between MLR and cardiovascular diseases (CVD) and all-cause mortality were assessed by multivariable Cox models.ResultsA total of 216 patients were included (mean age 57.65 ± 15.68 years, 42.13% male patients). Patients were divided into the low MLR group (<0.49) and the high MLR group (≥0.49). The levels of neutrophil and serum iron and the number of deaths were significantly higher in the high MLR group (P < 0.05). Spearman’s analysis showed that MLR was positively correlated with BUN (R = 0.210, P = 0.002), WBC (R = 0.178, P = 0.009), and neutrophil (R = 0.237, P < 0.001). Kaplan–Meier analysis showed that patients in the low MLR group present longer survival (64.08 ± 2.30 vs. 51.07 ± 3.12 months, P < 0.001). Multivariate Cox regression analysis showed that age, diabetes, and MLR (all P < 0.05) were factors significantly associated with a higher risk of CVD and all-cause mortality.ConclusionsOur results showed that high MLR values are an independent risk factor for CVD and all-cause mortality in patients initially receiving hemodialysis, especially in the elderly and those with a history of diabetes.